Iron-chelating, free radical scavenging and anti-proliferative activities of Azadirachta indica - Kanjana Pangjit (2018)
Background: Excessive production of reactive oxygen species leads to oxidative stress which occurs in various diseases, such as diabetes, cancer, neurodegenerative diseases, and secondary iron overload in thalassemia. Antioxidants are compounds that inhibit the oxidative processes and delay or suppress oxidative stress. Phytochemicals in herbs are interesting sources of natural antioxidants with cancer preventive properties. The use of natural products is beneficial for the prevention and/or treatment of oxidative stress mediated diseases. Objective: The study aimed to investigate the antioxidant and anti-proliferative properties of ethanolic extract from Azadirachta indica (neem) leaves. Material and Method: Neem leaves were extracted by 80% ethanol (v/v). The ethanolic extract was tested for free radical scavenging activity by 2, 2'-azino-bis-3-ethylbenzothiaziline-6-sulfonic acid (ABTS) and for the reduction of the power of ferric ion (Fe 3+ ) to ferrousion (Fe 2+ ) by ferric reducing antioxidant plasma (FRAP) assay. Furthermore, the ability of ironbinding activity was investigated by the spectrophotometry technique. The inhibitory effect on the growth of human promyelocytic leukemic cell line (HL-60 cells) was determined by MTT assay. Results: The ethanolic extract from neem leaves exhibited free radical scavenging activities and reduced the power of ferric ion (Fe 3+ ) to ferrous ion (Fe 2+ ) in dose responses. Furthermore, it was able to bind with iron rapidly within 5 minutes. Interestingly, this extract inhibited human promyelocytic leukemic cell line (HL-60 cells) growth in concentration response (0- 500 μg/ml) for 24 hour treatment. Conclusion: The ethanolic extract from neem leaves had strong antioxidant activity and an anti-proliferative effect on cancer cells.